2014
DOI: 10.1148/rg.342135057
|View full text |Cite
|
Sign up to set email alerts
|

Digital Tomosynthesis of the Chest: Current and Emerging Applications

Abstract: Digital tomosynthesis (DTS) of the chest is a technique whose basic components are similar to those of digital radiography, but that also provides some of the benefits of computed tomography (CT). The major advantages of DTS over conventional chest radiography are improved visibility of the pulmonary parenchyma and depiction of abnormalities such as pulmonary nodules. Calcifications, vessels, airways, and chest wall abnormalities are also much more readily visualized at DTS than at chest radiography. DTS could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…9,12,28 DTS imaging excludes overlapping anatomy, such as vasculature and ribs, and allows a clear view of the lung parenchyma, increasing the conspicuity of pulmonary nodules and providing greater sensitivity. 29,30 In addition to reductions in anatomical noise or composite artefacts, DTS provides greater depth and contrast resolution. 7 Our findings for per-patient data showed that the high diagnostic accuracy of DTS is complemented by greater homogeneity and consistency of results compared with chest radiography.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,28 DTS imaging excludes overlapping anatomy, such as vasculature and ribs, and allows a clear view of the lung parenchyma, increasing the conspicuity of pulmonary nodules and providing greater sensitivity. 29,30 In addition to reductions in anatomical noise or composite artefacts, DTS provides greater depth and contrast resolution. 7 Our findings for per-patient data showed that the high diagnostic accuracy of DTS is complemented by greater homogeneity and consistency of results compared with chest radiography.…”
Section: Discussionmentioning
confidence: 99%
“…The main application of chest DT to date has been improving detection of pulmonary nodules compared with conventional radiography (6,24,25), although DT may have other potential uses (7,8), including evaluation of suspected interstitial lung disease and pulmonary mycobacterial disease (26) and metastases (27), early detection of infection in immune-compromised patients, detection of subtle pneumothoraces, visualization and scoring of cystic fibrosis (28,29), airway visualization (30), detection of cardiac or coronary artery and aortic calcification (31), and evaluation of rib, spine, and clavicle fractures or other osseous lesions. According to studies that used CT as the reference standard, pulmonary nodules were definitely visible with higher sensitivity at DT than at posteroanterior chest radiography (25); more pulmonary nodules, particularly less than 9 mm in diameter, were detected with DT than with posteroanterior and lateral chest radiography (24).…”
Section: Chest Imagingmentioning
confidence: 99%
“…Manufacturers, such as Hologic and GE Healthcare, offer upgrade paths for standard mammography systems to become breast tomosynthesis capable. Other than DBT, DT is also advantageous in a variety of clinical contexts, including chest, head and neck, orthopedic, and emergency imaging (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The aims of this article are (a) to provide radiologists and radiologic technologists with knowledge about the basic facts and acquisition technique of DT, (b) to illustrate whole-body applications of DT by presenting a broad variety of clinical images, and (c) to demonstrate the clinical utilities and limitations of DT for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…Digital tomosynthesis (DTS) is a new diagnostic tool that produces sectional images using a moving X-ray tube, a flat digital panel, and a special reconstruction algorithm (Dobbins and Godfrey, 2003). Recently, DTS has been used to evaluate breast (Conant, 2014), lung (Chou et al, 2014), and musculoskeletal disease (Aoki et al, 2014). In musculoskeletal applications, DTS allows 20-to 50-fold dose reductions compared to that of CT.…”
Section: Introductionmentioning
confidence: 99%